THE EFFECT OF ENDOPLASMIC RETICULUM STRESS-REDUCING AGENTS ON LEPTIN SENSITIVITY IN OBESE WOMEN (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Obesity-related leptin resistance in women involves endoplasmic reticulum (ER) stress as a key pathological mechanism. This study investigates how ER stress-reducing compounds-including taurine, resveratrol, quercetin, and curcumin-restore leptin sensitivity through modulation of cellular stress markers. By attenuating GRP78, XBP1, and CHOP expression, these bioactive agents improve leptin receptor signaling and metabolic outcomes, suggesting potential therapeutic applications for obesity management in women.